Uncovering the impact of digital transformation on corporate environmental responsibility: Evidence from China - Jie Zhang; Olga P. Nedospasova (Управленец)
Under the current turbulent global situation, digital transformation has become a key force in restructuring the elements of world resources and new kinetic energy to promote the sustainable development of firms. In contrast, its internal and external driving factors at the firm level have not yet been identified. This study is dedicated to examining the impact of digital transformation on corporate environmental responsibility. The methodological foundations of the research are resource-based view, stakeholder theory, and information asymmetry theory. For verifying the proposed hypotheses, the study takes the panel data of Chinese listed firms from 2014 to 2023 (6,483 observations) as the research sample. It adopts statistical and regression analysis methods. Empirical results suggest that digital transformation positively correlates with corporate environmental responsibility by increasing companies’ engagement in green practices; economic policy uncertainty negatively moderates the analysed relationship, reducing the positive effect of the introduction of new technologies; media attention and financial constraints positively mediate the analyzed relationship. It is shown that the media serve as a key mechanism for external oversight and improving corporate governance in the capital market. By easing financial constraints, companies can obtain more external investment and resources, thereby increasing their ability to assume environmental responsibility.